Chronic treatment with a selective 5-HT6 receptor antagonist alters the behavioral and neurochemical effects of ethanol in young adult rats. Issue 2 (April 2016) - Jayarajan, Pradeep; Nirogi, Ramakrishna; Shinde, Anil; Benade, Vijay; Muddana, Nageswara Rao
Abstract : Experimental evidence indicates a potential role of 5-HT6 receptors in the regulation of addictive behavior. We studied the effects of a potent and selective 5-HT6 receptor antagonist (compound A) on voluntary ethanol intake and behavioral/neurochemical changes induced by ethanol. The pharmacokinetic interaction of compound A and ethanol was assessed. The effect of compound A on schedule-induced ethanol polydipsia was studied to determine its effect on voluntary ethanol intake. Open-field and ethanol-induced loss of righting reflex assays were carried out to determine the effect of compound A on the ataxic and sedative effects of ethanol. The effect on motor learning was evaluated using rotarod and brain microdialysis was carried out to study the effect on monoaminergic neurotransmission. No significant changes were observed in the pharmacokinetic parameters of compound A when cotreated with ethanol. Compound A significantly decreased voluntary ethanol consumption and attenuated the effects of ethanol on motor learning. Compound A also antagonized the sedative and ataxic effects of ethanol. The effect of ethanol on the dopaminergic and noradrenergic neurotransmission was blocked by compound A. The effects of compound A were evident only after chronic treatment. Compound A may have attenuated the behavioral effects of ethanol by blocking the ethanol-induced efflux of dopamine and norepinephrine in the motor cortex.